THE MAIN GEOMORPHOSITES OF THE EGADI ISLANDS (SICILY, ITALY) - Massoli-Novelli , Raniero (Alpine and Mediterranean Quaternary, 2005)
R. Massoli-Novelli, The main geomorphosites of the Egadi Islands (Sicily, Italy). (IT ISSN 0394-3356, 2005). This article describes the main geological and geomorphological features of the three main Egadi Islands: Favignana, Levanzo and Marettimo. These islands, which are essentially made up of Mesozoic carbonate rocks, are considered as the continuation in the sea of the north-western Sicilian chain. In addition, the main geomorphosites of these three islands are identified for the first time: these are the numerous, significant coastal caves. Particular emphasis is given to natural and anthropogenetic geomorphosites related to the Pleistocene bioclastic calcarenite caves present in Favignana, an ancient site of intense quarrying activities.